TINDAK PIDANA KEKERASAN SEKSUAL (PERSPEKTIF PERBANDINGAN HUKUM ISLAM DAN HUKUM POSITIF) - Kalsum, Ummu; Syafii, Ahmad; R. Massi, Randy Atma (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2024)
Sexual violence against women continues to occur to this day, with the increasing cases of sexual violence against women becoming one of the topics frequently discussed and examined by society. Various efforts and studies have been conducted to address and reduce the number of sexual violence incidents against women. Sexual violence is increasingly alarming because it impacts the victims, making them feel threatened, humiliated, scared, ashamed, and so on. This research uses Normative Juridical research (normative legal research method) with a qualitative approach. Additionally, this research also employs a Legislative approach and a Comparative approach. The data collection technique is conducted through document/literature study, where the research objects are primary, secondary, and tertiary legal materials. All forms of sexual violence are subject to criminal penalties, and Law Number 12 of 2022 concerning Sexual Violence Crimes has clearly regulated this issue. In Islamic law, the sanctions given are in the form of ta'zir punishment. Ta'zir punishment includes all penalties other than hudud and qisas, but the punishment may be more severe and encompass more than hudud and qisas. According to the Syafi'i School, the sanctions can include diyat (compensation) accompanied by mahar (mithil), as well the had zina for the perpetrator.